O movimento emancipacionista de Minas do Norte: uma identidade territorial em questão - Pires, Warley Pereira (2006)
The new federated unit s demand new states has been recurrent in Brazil, especially from the 80 s decade. The fight for the emancipation of regions discriminated politics, economic and culturally had its acme on the 1988 Federal Constituent and on the Constitutional revision in 1993. Based on the Constituent and on the example of Tocantins, many movements have sought the emancipation through the solicitation of plebiscites. In the centre of this process, we show up the emancipationist movement of Minas do Norte, called before São Francisco, which has as objective the creation of a state with the same name, covering the mineiras regions from the Minas Gerais north, Vale do Jequitinhonha and Mucuri. The justifications to this emancipation are based on the economic regional lateness, the politics discrimination and on a complex identity/cultural demand, which will be studied on this work. So, we try to discuss the movement from the demand of a cultural identity in regional level, what now makes its differentiation from the other states of Minas Gerais.